Intercellular communication for innate immunity. (June 2017) - Nguyen, Tan A.; Pang, Ken C.; Masters, Seth L.
Highlights: Viral RNAs are incorporated into exosomes of infected cells and are exported to neighbouring cells to induce type I IFN. cGAMP is transferred via gap junctions or incorporated into exosomes/viral particles to induce STING-mediated type I IFN. Extracellular ASC specks from pyroptotic cells are phagocytosed by macrophages to induce bystander inflammasome activation. Abstract: An effective innate immune response relies on the detection of pathogen associated molecular patterns (PAMPs) by various host pattern recognition receptors (PRRs) that result in the production of pro-inflammatory cytokines and chemokines. Viruses and bacteria have co-evolved with the immune system and developed multiple strategies to usurp or circumvent host machinery and blunt the innate immune response in infected cells. Recently, it has become apparent that infected or dying cells can transmit PAMPs and host PRR signalling proteins to uninfected bystander cells to thereby bypass pathogen evasion strategies, and potentiate innate immune signalling. This bystander activation of innate immunity represents an alternative method by which the host can control infections via cell-to-cell communication. In this review, we discuss what is currently known about the intercellular transfer of pathogen- or host-derived RNA, DNA and proteins from infected cells to neighbouring cells and how this impacts on host innate immunity.